Breast cancer identification and prognosis with machine learning techniques - An elucidative review. Issue 2 (17th February 2020) - Kumar, Mohan; Khatri, Sunil Kumar; Mohammadian, Masoud
Abstract: Cancer is the principle wellspring of death around the globe with 2.09 million cases so far in 2018 [1]. Around 627000 deaths accounting to 6.6% are caused because of female breast cancer and it ranks five amongst the list of top causes for deaths, the prime reason being prognosis being favorable in developed countries. The timely empathy of breast cancer further makes the process of prognosis better hence improving the rates of survival, because this will indorse on time treatment which is given clinically to patients. When the classification is done in an accurate way for malignant and benign tumours, it stops the suffering of patients with excessive ailments. The best possible recognizable proof of breast cancer disease and the process of characterizing into benign and malignant groups is that the main concern of a ton of investigation and research. When thrown light on its particular advantages in significant alternatives recognition from the datasets of entangled breast cancer, the generally perceived option is Machine Learning, because of the philosophy of determination in breast cancer to arrange pattern and forecast modelling. This paper will in general, survey machine learning and assessment of this particular paper, WBCD: Wisconsin Breast Cancer Database has been used as the benchmark dataset.